Edukasi Kesehatan Tentang Pengaruh Pemakaian Diapers Yang Menyebabkan Ruam Popok (Diaper Rash) Terhadap Ibu Di Klinik EvieTahun 2022 - Ade Rachmat Yudiyanto; Damayanty S; Ingka Kristina Pangaribuan (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
Diaper rash is a complaint of red spots on the genitals and buttocks of babies wearing diapers caused by skin rubbing against diapers (Dwi Maryanti, et al, 2011). Diaper rash often occurs in the area around a baby's buttocks due to the use of diapers that are rarely changed, are too tight, or are used for too long. Usually the rash is not dangerous, but it can cause pain and cause anxiety in the baby and parents. According to a report by the Journal of Pediatrics, there were 54% of babies aged 1 month who experienced diaper rash after using "disposable diapers", which were first made by Victor Miller in 1950 under the name pampers and are popular throughout the world. At first, mothers hoped that their babies would be comfortable and stay dry.but in the end the baby experiences diaper rush (diaper rash) and the incidence of diaper rash in babies who use disposable diapers increases to 61% Diaper rash in Indonesia is a skin problem in infants and children. Diaper rash, according to Dr. Siti Aisah Boediarjo, Sp. KK, is a skin disorder in the form of red, inflamed patches. Sometimes accompanied by hard, scaly skin, nodules, even blisters and blisters, which cause itching and burning in babies, approximately 50% of babies and children who wear diapers have experienced a diaper rush. The method of implementing this activity is: providing education or counseling to mothers who have children and still use diapers, distributing leaflets and explaining the use of diapers so that diaper rash does not occur. This activity begins with the preparation of proposals and activity administration and continues with an assessment of the situation. In August 2021 activities were carried out at the Evie Kec Babalan Clinic, Langkat Regency